Dexamethasone as a ropivacaine adjuvant to pre‐emptive incision‐site infiltration analgesia in pediatric craniotomy patients: A prospective, multicenter, randomized, double‐blind, controlled trial. Issue 6 (23rd March 2021) - Zhao, Chunmei; Zhang, Nijia; Shrestha, Niti; Liu, Hongbing; Ge, Ming; Luo, Fang
Abstract: Background: Dexamethasone added to incision‐site infiltration has been routinely used to reduce pain after tonsillectomy in children. However, this has not been studied in pediatric craniotomy patients yet. We hypothesized that incision‐site infiltration with a combination of ropivacaine and dexamethasone might provide superior analgesia to ropivacaine alone in pediatric craniotomy patients. Methods: In this multicenter, double‐blind, randomized, controlled trial, children aged 2–12 years, scheduled for craniotomy, were prospectively enrolled at two study centers, from September 2, 2019, to July 5, 2020. Eighty children were randomly assigned (1:1) to either ropivacaine plus dexamethasone group who received pre‐emptive incision‐site infiltration with 0.2% ropivacaine plus 0.025% dexamethasone, or ropivacaine group who received 0.2% ropivacaine alone. Primary outcome was the modified Children's Hospital of Eastern Ontario Pain Scale (mCHEOPS) at 24 h postoperatively. Primary analysis was performed using the modified intention‐to‐treat principle. Results: Pre‐emptive incision‐site infiltration with ropivacaine plus dexamethasone had a reduced pain score of 2.0, compared with the pain score of 2.9 in the ropivacaine group, at 24 h postoperatively (mean difference −0.9, 95% confidence interval [CI], −1.7 to −0.2; p  = .019). Estimated median of the time of first rescue analgesic demand was 24 h in the ropivacaine plus dexamethasone group and 8.5 h in the ropivacaine group [hazard ratio 0.43, 95% CI 0.24 to 0.08; Log‐rank p  = .0025]. No adverse events related to incision‐site infiltration with dexamethasone were observed in this study. Discussion: Dexamethsone reduces the local production of pro‐inflammatory factors after tissue damage and as a ropivacaine adjuvant for incision‐site infiltration reduced the pain scores by 31% at 24 h postoperatively. The results were similar to several prior studies on to tonsillectomy patients. However, this changes on pain scores might has limited clinical significance. Conclusions: The addition of dexamethasone to ropivacaine for preoperative incision‐site infiltration has better postoperative analgesic effect than ropivacaine alone in pediatric craniotomy patients.